2020
DOI: 10.1097/md.0000000000021261
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinicopathologic profiles and prognosis of gastric cancer in the upper, middle and lower third of the stomach

Abstract: Gastric cancer (GC) is the fourth most common cancer in the world and the second most common cancer in China. The aim of this study was to investigate the clinicopathologic profiles and prognosis of GC in the upper third (UT), middle third (MT) and low third (LT) of the stomach. Five hundred and forty-two patients with GC resected between January 2010 and January 2014 were retrospectively studied and divided in 3 groups according to cancer location: upper third gastric cancer (UTGC) (n = 62); MTGC (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In the previous study, we reported the clinicopathologic characteristics and prognosis of GC patients with different tumor locations in Qinghai Province located in the North-Western China, showing that upper third GC is distinct from the lower third GC whereas middle third GC shares some characteristics from both upper third GC and lower third GC. [ 10 ] In the present study, we compared the age-specific clinicopathologic characteristics and prognosis of GC and found that young GC patients was predominant in women, EGC of macroscopic types, T1 of T staging and low or non-differentiation degree compared with old GC patients.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In the previous study, we reported the clinicopathologic characteristics and prognosis of GC patients with different tumor locations in Qinghai Province located in the North-Western China, showing that upper third GC is distinct from the lower third GC whereas middle third GC shares some characteristics from both upper third GC and lower third GC. [ 10 ] In the present study, we compared the age-specific clinicopathologic characteristics and prognosis of GC and found that young GC patients was predominant in women, EGC of macroscopic types, T1 of T staging and low or non-differentiation degree compared with old GC patients.…”
Section: Discussionmentioning
confidence: 77%
“…[ 2 ] We previously analyzed the clinicopathologic characteristics and prognosis of GC patients with different tumor locations in Qinghai Province and found that GC in upper third of the stomach is distinct from the lower third GC whereas middle third GC shares some characteristics from both upper third GC and lower third GC. [ 10 ] However, few studies reported the incidence and prognosis of young GC in the province. The present study was designed to compare the clinicopathologic characteristics and prognosis of GC in patients ≤40 and >40 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Like our results, several studies also showed that the tumor location of gastric cancer was an independent prognostic factor; additionally, the upper location was associated with worse prognoses. Recently, Ma et al (2020) reported that the 5-year OS for patients with gastric cancer (stages I-III, 542 cases) located in the upper, middle, and lower third of the stomach were 35.0, 43.2, and 51.4%, respectively (11). With the tumor stage similar to Ma's, some studies with similar results were (14).…”
Section: Discussionmentioning
confidence: 90%
“…Recently, Ma et al. (2020) reported that the 5-year OS for patients with gastric cancer (stages I–III, 542 cases) located in the upper, middle, and lower third of the stomach were 35.0, 43.2, and 51.4%, respectively ( 11 ). With the tumor stage similar to Ma’s, some studies with similar results were published earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Although the TNM stage is frequently used to predict the prognosis of patients, it is observed that patients with the same TNM stage progress differently. In addition to the TNM stage, many variables such as pathophysiological classi cation, tumor differentiation, serosa involvement, and lymphovascular invasion have been shown to affect the prognosis of the disease [2,3]. Although these factors have been shown to affect gastric cancer prognosis, there is no single marker that can predict survival in patients with metastatic gastric cancer.…”
Section: Introductionmentioning
confidence: 99%